2022
DOI: 10.1186/s12950-022-00299-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of two different dietary regimens during exercise on outcome of experimental acute kidney injury

Abstract: Background Acute kidney injury (AKI) is a syndrome characterized by rapid loss of excretory function of kidney. Both exercise and some diets have been shown to increase silent information regulator (SIRT1) expression leading to reduction of kidney injury. In this study, the effect of two different diets during exercise on kidney function, oxidative stress, inflammation and also SIRT1 in AKI was investigated. Materials and methods A number of rats w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Better physical condition of exercised animals may lead to better hemodynamic and metabolic conditions and ultimately activation of molecular mechanisms of cell survival in kidney tissue [ 49 ]. SIRT1 expression was reduced in the AKI model [ 1 ], and it was shown that exercise reduces apoptosis by increasing SIRT1 expression [ 50 ]. SIRT1 is an evolutionary biological stress response that is associated with increased long-term function and survival of vital cell types [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better physical condition of exercised animals may lead to better hemodynamic and metabolic conditions and ultimately activation of molecular mechanisms of cell survival in kidney tissue [ 49 ]. SIRT1 expression was reduced in the AKI model [ 1 ], and it was shown that exercise reduces apoptosis by increasing SIRT1 expression [ 50 ]. SIRT1 is an evolutionary biological stress response that is associated with increased long-term function and survival of vital cell types [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a complex clinical dysfunction that is accompanied with increased serum urea and creatinine and decreased glomerular filtration rate (GFR), [ 1 ]. Despite technological progresses in the treatment of renal failure, AKI continues to have unfavorable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise can offer benefits to autistic individuals through rhythmic movements that are similar to stereotyped behaviors. Researchers have found that exercise can reduce repetitive behaviors, but this knowledge is often marginalized [ 15 , 16 ]. Intense exercise stimulates oxidative stress, but regular and MIT lessens oxidative stress by increasing antioxidant defense, ultimately reducing the symptoms of autism.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that treadmill exercise at low speeds (up to 8 m/min) could positively affect motor and cognitive disorders in autistic rats [ 19 , 20 ]. Also, in another study, treadmill exercise at moderate speeds (up to 25 m/min) could improve neurological deficits such as autism [ 16 ]. The effects of exercise in low and moderate intensities have been examined on autism, but no comparison has been made between these two types of exercise intensity in the two sexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TBI is related to the progression of acute renal failure (ARF). Systemic inflammation following trauma and the onset of cytokine cascade due to brain injury may impair blood flow to body organs and excretory function [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%